2
(x+2) - x (x+5)=2 (x-7)
Răspunsuri la întrebare
Răspuns de
1
2(x+2) - x (x+5)=2 (x-7)
2x+4-x²+5x=2x-14
x²+5x=10
2x+4-x²+5x=2x-14
x²+5x=10
Adi4344444:
multumesc !
Răspuns de
1
2x+4 - x^2 - 5x= 2x-14
4 - x^2 - 5x + 14 = 0
-x^2 - 5x + 18 = 0
Δ = b^2 - 4ac
Δ = 25 - 4(-1)(18) = 25 + 72 = 97
x1,2 = (-b+- √Δ)/2a => x1= (5+
)/ -2 si x2 = (5+
)/ -2
4 - x^2 - 5x + 14 = 0
-x^2 - 5x + 18 = 0
Δ = b^2 - 4ac
Δ = 25 - 4(-1)(18) = 25 + 72 = 97
x1,2 = (-b+- √Δ)/2a => x1= (5+
Alte întrebări interesante
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Fizică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă